2003
DOI: 10.1099/mic.0.26125-0
|View full text |Cite
|
Sign up to set email alerts
|

Patchiness of murein insertion into the sidewall of Escherichia coli

Abstract: This paper extends, with computer techniques, the authors' previous work on the kinetics of pole wall and sidewall synthesis in Escherichia coli. These findings extend the conclusion that the nascent poles are made of entirely new material and that no new material is inserted into old poles. This requires re-evaluation of ideas in the literature about wall growth and cell division. Mechanisms of various types have been suggested for the growth of Gram-negative rod-shaped bacteria and these will also require ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Bidirectional peptidoglycan chain synthesis also suggests that if PGTs are found in multiprotein complexes, as proposed (19), then the complexes remain stationary at biosynthetic loci rather than sliding along the membrane surface. Recent observations that new peptidoglycan is incorporated in patches throughout the bacterial sacculus (20) are consistent with such a model. It is not yet known whether catalytically active monomers can be produced if the dimerization interface is disrupted, but the structure reported here provides a basis to guide the design of experiments to address the functional role, if any, of dimerization by class A PBPs.…”
Section: Resultssupporting
confidence: 63%
“…Bidirectional peptidoglycan chain synthesis also suggests that if PGTs are found in multiprotein complexes, as proposed (19), then the complexes remain stationary at biosynthetic loci rather than sliding along the membrane surface. Recent observations that new peptidoglycan is incorporated in patches throughout the bacterial sacculus (20) are consistent with such a model. It is not yet known whether catalytically active monomers can be produced if the dimerization interface is disrupted, but the structure reported here provides a basis to guide the design of experiments to address the functional role, if any, of dimerization by class A PBPs.…”
Section: Resultssupporting
confidence: 63%
“…To determine whether the regions enriched in MreB experienced higher levels of cell wall growth, we developed a method to quantify local cell growth. Previous single time-point electron microscopy studies suggested that new cell wall is incorporated in patches along the cylindrical cell surface (25). We reasoned that if cell surface growth is sufficiently heterogeneous, any label that binds with high affinity, is locally stationary, and has a long fluorescence lifetime could serve as a fiducial marker of cell growth in a time-lapse pulse-chase experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Peptidoglycan comprising the poles is, in some way, different from that in the lateral walls (52,53,55). This polar peptidoglycan is "inert" in that it is neither degraded and recycled nor diluted by addition of new material (43,52,171).…”
Section: Sequestrationmentioning
confidence: 99%